A outorga pelo uso dos recursos hídricos no Estado do Amazonas - Nascimento, Daniel Abrahão do (2012)
The water is a determining factor in the lives of the people of the Amazon and on your biome. Despite being plentiful in the Amazon, paradoxically in certain circumstances is scarce. The urban agglomerations with the pressures of human impact on the environment is the main factor that alters water quality, affecting access to and use of environmental goods as essential to life in every way. The Amazon is a scenario marked by the abundance and at the same time by the shortage. A scenario in which at the same time water is source of life and again is the cause of death. The form of ownership and management of water is critical to define its preservation or pollution. Brazilian law provides for the protection and water management. It remains to be seen whether this legislation homeland and the instruments of management of water resources are sufficient and meets the resolution of various conflicts generated by the use or appropriation of water in a peculiar reality that is Amazon. Is there a way to manage water in a scene of abundance and territorial dimensions and different from those that inspired the making of protective law and Manager? Will the local government is able to manage its waters through the adoption of a model itself, or will have to join the imported that is incompatible with its dimensions? For this, the present study examines one of the instruments of the national water resources Policy, the grant in the State of Amazonas. Through the grant will ensure the quantitative and qualitative control of the uses of the water and the effective exercise of the right of access to water. In addition to propose suggestions on how to best deploy the policy and the State water resources Management in the State of Amazonas linked to sustainable development and environmental protection. Word-key: